(Invisible) Displays of Survivalist Intensive Motherhood among UK Brexit Preppers. (December 2021) - Kerrane, Ben; Kerrane, Katy; Bettany, Shona; Rowe, David
This article explores mothers' narratives of 'prepping' behaviours. Prepping involves the management of stockpiled household items in anticipation of marketplace disruption. In this article, we use anticipated food shortages following the UK's exit from the EU ('Brexit') as our context. Drawing on interview data, we highlight how mothers embed prepping into their ongoing pursuit of intensive motherhood, bound in the highly gendered practice of feeding the family. While adhering to elements of intensive motherhood ideology (their actions are labour intensive/child centred), participants reveal a hidden element to their practice. We introduce the notion of 'survivalist intensive motherhood' to understand their actions. Survivalist intensive motherhood departs from earlier intensive motherhood studies due to the largely invisible nature of preparations and the trade-offs made to feed the family during resource scarcity.